How can the environmental efficiency of Indonesian cocoa farms be increased? - Andras Tothmihaly; Stephan von Cramon-Taubadel; Verina Ingram (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
We look at the trade-off between smallholder cocoa intensification and the ecosystem in Indonesia and investigate the determinants of environmental efficiency in cocoa production. In our analysis, we apply a distance output function that includes cocoa production and the abundance of native rainforest plants as outputs. Our data set, based on a household and environment survey conducted in 2015, allows us to analyze 208 cocoa producers with both measured and self-reported data. We find that the intensification of cocoa farms results in higher ecosystem degradation. Additionally, the estimations show substantial mean inefficiencies (50 percent). On average, the efficiency scores point to a possible production expansion of 367 kg of cocoa per farm and year, to a possible increase of 43680 rainforest plants per farm, or to a possible acreage reduction of 0.52 hectares per farm. Finally, our results show that agricultural extension services have a substantial role in increasing efficiency.
Keywords: O13; Q01; Q12; 330; cocoa production; Indonesia; environmental efficiency